2022
DOI: 10.3390/buildings12020098
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Appropriate Risk Response Strategies Considering Utility Function and Budget Constraints: A Case Study of a Construction Company in Iran

Abstract: Successful implementation of construction projects worldwide calls for a set of effective risk management plans in which uncertainties associated with risks and effective response strategies are addressed meticulously. Thus, this study aims to provide an optimization approach with which risk response strategies that maximize the utility function are selected. This selection is by opting for the most appropriate strategies with the highest impact on the project regarding the weight of each risk and budget const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 69 publications
0
19
0
1
Order By: Relevance
“…However, the failure of many construction projects in meeting deadlines, cost and quality targets is continuously on the rise and there are signs of accentuating year after year suffering significant financial losses of construction works in Kenya. The successful implementation of construction projects worldwide calls for a set of effective risk management plans (Safaeian et al, 2022). However, the effective implementation of risk management practices has been overlooked in developing nations (Shayan, Pyung Kim, & Tam, 2022).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the failure of many construction projects in meeting deadlines, cost and quality targets is continuously on the rise and there are signs of accentuating year after year suffering significant financial losses of construction works in Kenya. The successful implementation of construction projects worldwide calls for a set of effective risk management plans (Safaeian et al, 2022). However, the effective implementation of risk management practices has been overlooked in developing nations (Shayan, Pyung Kim, & Tam, 2022).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The project risk identification addresses need of appreciation of risks (Obondi, 2022), by identifying what might happen considering all possible causes and scenes that indicate potential consequences (Sarkar & Singh, 2022). However, despite the various definitions of project risk identification, it is surprising that there is no unanimous definition that all researchers agree on (Safaeian et al, 2022).…”
Section: Risk Identificationmentioning
confidence: 99%
“…Risk management is an important exercise in order to achieve better performance of projects (Chepkoech & Wairimu, 2023). However, many a times, projects fail to keep up with the planned schedules and budgeted costs to meet their goals (Shafiuddin et al, 2022;Safaeian, Fathollahi-Fard, Kabirifar, Yazdani, & Shapouri, 2022). The existing literature suggests that there is a consensus between academia and industry that project risk management is critical to project success (Aramali, Sanboskani, Gibson Jr, El Asmar, & Cho, 2022;Ahmad et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have an interest in meta-heuristic algorithms due to their effectiveness and applicability in solving real-world problems [ 24 , 25 , 26 , 27 ]. Therefore, they have been used in many different research areas [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. This paper utilizes GA and PSO, which have been extensively used in literature reviews for various types of vehicle routing problems [ 39 ], and they have demonstrated their capability in handling complex problems [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%